Environmental impact assessment of rice mill waste valorisation to glucose through biorefinery platform - Abu-Bakar, Nurul Ain; Roslan, Ahmad Muhaimin; Hassan, Mohd Ali; Abdul Rahman, Mohammad Hariz; Ibrahim, Khairul Nadiah; Abd Rahman, Muhammad Daaniyall; Mohamad, Rozyanti (Springer Science and Business Media, 2023)
Environmental impact assessment of glucose production from paddy milling waste, known as empty and partially filled paddy grain (EPFG) in Malaysia, was performed using life cycle assessment (LCA). Three scenarios were conducted based on system expansion of the process. The LCA was conducted using ReCiPe methodology at midpoint and endpoint levels. The results indicate that enzymatic hydrolysis phase is the hotspot in the conversion system due to enzyme production. In addition, the agriculture phase also contributed to negative impacts, especially towards climate change. An improved environmental load was observed in scenario 2 when all EPFG fractionation was utilised to replace fossil-based electricity. Sensitivity analysis showed an increase in glucose yield leads to reduced environmental impact. Thus, the LCA study suggests that the conversion process of EPFG could further benefit and improve the paddy industry waste management with low impact contribution to the environment compared to other feedstock used for glucose production.